IMPACT OF CLIMATE CHANGE ON AVAILABILITY OF SURFACE WATERS IN SOUTH AMERICA - Pérez-Campomanes, Giovene (2020)
In the present work, a review was made of the current state of the assessment of the climate impact on the availability of surface waters in South America. A review of 72 scientific articles refereed and indexed during the period 2010 to 2019 of 10 countries was made: Argentina, Bolivia, Brazil, Colombia, Chile, Ecuador, Paraguay, Peru, Uruguay, and Venezuela. Scientific articles in Spanish, English and Portuguese were reviewed. It was obtained that the variables related to the topic were 28, of which 7 were the main ones: climate change, rain, vulnerability, climatic variability, hydrological modeling, water regulation, and rural development. It was observed that there is an increase in the number of scientific articles carried out in the last five years, reflecting the interest of South American countries in the presence of climate change and its iIn the present work, a review was made of the current state of the assessment of the climate impact on the availability of surface waters in South America. A review of 72 scientific articles refereed and indexed during the period 2010 to 2019 of 10 countries was made: Argentina, Bolivia, Brazil, Colombia, Chile, Ecuador, Paraguay, Peru, Uruguay, and Venezuela. Scientific articles in Spanish, English and Portuguese were reviewed. Twenty-eight articles were obtained that fit the variables related to the topic of which 7 were the main ones: climate change, rain, vulnerability, climatic variability, hydrological modeling, water regulation, and rural development. It was observed that there is an increase in the number of scientific articles carried out in the last five years, reflecting the interest of South American countries in the presence of climate change and its impact on the availability of surface waters. Colombia and Brazil presented the highest number of scientific articles. Research has been carried out in hydrographic basins in South America, and their behavior has been simulated, through the use of mathematical models. Surface waters for agricultural use were investigated in the upper part of the basins and in the city for the consumption of the population. Generally it is in times of scarcity of the water resource that the planning is carried out. The characteristics of each basin, the behaviors and customs of the inhabitants of the upper basin must be included, as well as all the users involved in the use of the water resource. It is important that the governments of the countries of South America continue promoting scientific research in this area. Key words: basin – rain – temperature – water resource – vulnerability